(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the outcome of upper ureteric stone management using semirigid URS + ICPL. Materials and Methods: Patients undergoing URS + ICPL in patient department were included in the study. Total 38 patient were included in the study from March 2009 to June 2010 in National Institute of Kidney diseases & Urology, Dhaka. Stone size was 8 mm to 1.5 cm, patients were with good renal function, well excreation on both side, without any distal obstruction, infection or multiple ureteric calculi. The procedure was done under SAB.Cystoscopy was done for identification of ureteric orifice and guide wire was passed within ureteric orifice under visual monitoring.46 cm 10 Fr Storz Uretroscope was advanced next to the guide wire.At time a tortuous portion of the ureter was encountered a second guide wire was helpful. As soon as the stone was seen the pneymatic probe was pushed toward the stone.After fixing to the stone, pneumatic source was on and stone fragmentation was started. Care was taken to avoid injury of the ureter and keeping eye one stone fragment migration within the ureter was achieved. Placement of D-J stent was done at the conclusion of the procedure in most of the cases Result: The patients were followed upto 3 months post-operatively. Within immediate complications fever occured in 10 (26.3%) patients, severe haematurea occured in 8 (21.3%) patients, ureteral injury in 8 (21.3%) & ureteric perforation in 2 (4.8%) patients underwent URS+ ICPL. Stone clearance rate after 01 month of intervention was 30 (78.9%). Almost half of the patients developed UTI after 01 month of intervention. Pyelonephritis occured in 2 ( 4.8%) patient in this group. After 03 months of intervention 84.2% patients exibited complete clearance of stone. Only 02 (4.8%) patients developed ureteric stricture. Conclusion: For management of selective sized upper ureteric stone ureterorenoscopy with semirigid one using pneumatic source of energy is a good option for it’s high stone clearance & resonably low complications. Bangladesh Journal of Urology, Vol. 16, No. 2, July 2013 p.47-50